The development and microstructural evolution of the bulk yTi-45Al-2Nb (Sn Cr Mn & Si)-doped intermetallic alloys and their mechanical properties - Siyasiya, Charles Witness (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2019.